Influence of male age on producing rival calls in brown planthopper Nilaparvata lugens Stál (Homoptera: Delphacidae) - Ahmed, Agha Mushtaque; Muhamad Awang, Rita; Omar, Dzolkhifli; Majid, Dayang Laila; Gnanasegaram, Manjeri (AkiNik Publications, 2016)
Brown planthopper (BPH) Nilaparvata lugens is an imperative insect pest of rice crop throughout the Asia. Both BPH male and female rely on substrate borne vibrational signals prior to mate. Often such mating communication is affected by rivalry signals of other existed males of variable age and population. Therefore, the current study observed the effect of age and population density on production of male rival calls. The results illustrated that the male rival calls were only produced in the presence of other male. No single male rival call was produced when a pair of a matured male and female of five days old was placed on rice plant. However, production of rival calls increased with increasing the age of BPH male and maximum number of (90%) male produced rival calls at the age of fifth days. Similarly, the population density affected the behaviour of male for producing the rival calls. A maximum number of male produced rival calls, when population of seven virgin males were reared together prior to experiment. Such results showed that the presence of rivalry signals during mating communication is a crucial part of mating behaviour of brown planthopper and only observed among males. Understanding the influence of these factors on mating behaviour of BPH is essential as it serves as baseline for exploiting the mating signals of BPH to reduce the population density below the economic injury level.